Sales Promotion Produk Hijab Clothing di Instagram - Radhita Safira Kalimaya; Anne Ratnasari (UNISBA Press, 2022)
Abstract. The city of Bandung, is one of the cities where the creative hijab clothing industry develops. The development of this industry is inseparable from the efforts of business people to create, market and build their own brands in the Muslim fashion industry, especially hijab on social media, one of which is marketing products on Instagram. Hijab clothing that uses Instagram as a promotional medium is Deans Collection. In carrying out its promotion, Deans Collection uses Instagram media to carry out promotions such as holding giveaways, discounted prices, free shipping for buyers on the website and loyalty points. This study aims to identify and recognize sales promotion activities carried out on social media Instagram Deans Collection. The research method used in this research is a qualitative research method with a constructivist paradigm and a holistic single case study approach. By using this research method, the researcher wants to know how the sales promotion of Deans Collection hijab products on social media Instagram @deanscollection. Data collection techniques are carried out using interviews, observation, and documentation. The informants taken in this study were the Deans Collection owner as the owner of the hijab sales business, and the Content Creator Deans Collection as content creator on Instagram @deanscollection. In data analysis techniques, researchers used Miles and Guberman data analysis techniques. Abstrak. Kota Bandung, adalah salah satu kota tempat berkembangnya industri kreatif hijab clothing. Berkembangnya industri ini tidak terlepas dari upaya para pebisnis untuk membuat, memasarkan dan membangun merk sendiri dalam industri fashion muslim terutama hijab di media sosial, salah satunya melakukan pemasaran produk di instagram. Hijab clothing yang menggunakan instagram sebagai media promosi adalah Deans Collection. Dalam melakukan promosinya, Deans Collection menggunakan media Instagram untuk melakukan promosi seperti mengadakan giveaway, potongan harga, gratis ongkir khusus pembeli di website dan juga loyalty point. Penelitian ini bertujuan untuk mengetahui dan mengenal kegiatan sales promotion yang dilakukan pada sosial media Instagram Deans Collection. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian kualitatif dengan paradigma konstruktivis dan pendekatan studi kasus tunggal holistik. Dengan menggunakan metode penelitian ini, peneliti ingin mengetahui bagaimana sales promotion produk hijab Deans Collection pada media sosial Instagram @deanscollection Teknik pengumpulan data yang dilakukan menggunakan wawancara, observasi, dan dokumentasi. Informan yang di ambil dalam penelitian ini adalah owner Deans Collection selaku pemilik usaha penjualan hijab, dan Content Creator Deans Collection selaku pembuat konten pada Instagram @deanscollection Dalam teknik analisis data peneliti menggunakan teknik analisis data Miles dan Guberman.